The Seismotectonic Significance of Geofluids in Italy - Vannoli, Paola; Martinelli, Giovanni; Valensise, Gianluca (Frontiers in Earth Science, 2021)
There is growing interest in how geofluid emissions are released in the atmosphere by the planet’s geodynamic activity, and how much they contribute to the global budget of greenhouse gases. Many workers are addressing this issue with studies conducted at global scale, so as to get the required global-scale answers. The data available at the global scale on geofluids, faults, earthquakes and volcanoes, however, are generally too coarse to provide these answers. We investigate the relationships between geofluid emissions and tectonics at a more detailed scale. Building on over a century of data on geofluid emissions and on an extensive knowledge of the region’s tectonics and seismicity, we focused on Italy, one of the areas of the globe that experience the largest release of natural CO2 and CH4. We systematically overlaid and compared data collected by a number of workers into 13 published countrywide databases concerning geofluid emissions, carbon-bearing deposits, seismogenic faults, historical and instrumentally documented earthquakes, and heat flow observations. Our results indicate that 1) thermal springs and CO2 emissions dominate in areas of mantle upwelling and crustal stretching, but also that 2) some of them occur in the extending inner Apennines, generally along major lithospheric chain-perpendicular lineaments that bound the largest normal faults. Conversely, 3) CH4 emissions and mud volcanoes dominate in areas undergoing active contraction, where no CO2 emissions are observed; in particular, we find 4) that mud volcanoes concentrate where the crests of active anticlines intersect major lithospheric chain-perpendicular lineaments. An overarching conclusion is that, in Italy, the release of geofluids is primarily controlled by deep crustal discontinuities that developed over the course of 5–10 My, and is only mildly affected by ongoing crustal strains. Geofluid emissions bring information on processes that occur primarily in the lower crust, marking the surface projection of generally hidden discontinuities that control the geometry and modes of seismic release. As such they may also provide valuable insight for improving the assessment of seismic hazard in hard-to-investigate seismically active regions, such as Italy.